Determinants of human capital development: case of Malaysia / Shaliza Azreen Mohd Zulkifli ... [et al.] - Mohd Zulkifli, Shaliza Azreen; Zulkifli, Nur Mizatun Hasni; Muhamad Yusuf, Noor Hafizha; Eem, Chen Jen (2017)
As a developing country with upper-middle income status, Malaysia aspires to become high income status by 2020. Human capital utilization is vital for a country to achieve high income status. Even though development of human capital is one of the essential efforts that can give benefit toward individual, organization, economy and also country, Malaysia still needs to undertake structural changes in resolving longstanding problems like education. It is because education acts as a medium or foundation to human capital development. The need of high quality leaders to move forward and become more competitive nation does not only require talent but must be built continuously from within the education system. Structural changes which are revamping the education system would create challenges not only to the government but also learning institutions and most importantly the human capital. This study is undertaken to determine factors that affect human capital development in Malaysia. Using time series data which is from 1982 until 2014 that covers a period of 33 years, human capital development acts as a dependent variable while the independent variables are unemployment, education level, and foreign direct investment (FDI) and economic growth. The model of this study is tested through multivariate framework. It is found that education level has statistically significant relationship in determining human capital development.